Definition of Natural Languages Using Context-free Grammer: In Context of Dari Language - Asgharzada, Mahmood (American International Journal of Social Science Research, 2019)
Formal definition of a natural language lets computers understand it; the languages have challenging complexity to come under representation of any formal language. Modeling assumptions, using formal languages, we can approximate the languages; and better approximation we do, more complexities of formal languages are resolved. Objective is to study current researches and possibilities to model Dari as a context-free language. Researchers have worked for more than 6 decades on definition of syntax of natural languages using context-free grammer. It is crucial that computer scientists to be able to thoroughly understand about which category of formal languages the natural language exist in in. In overall, our skill to decide the grammar type of natural languages performs a significant role in our capability to parse it. This review article concludes that discussed issue of the context-freeness of a certain language is regularly reliant on upon the level of complexity of the language. The common of languages investigated in this regard are languages of European family and Indo-Aryan languages liker Dari, Arabic and Pashto have not been adequately fortunate to be devoted thorough researches in this regard.